Consumption patterns and perceived health benefits of underutilized legumes among women in selected local government areas of Niger State, Nigeria - Udofia, F.A.; Adepoju, O.T.; Chata, D.M.; Oyatomi, O.A.; Abberton, M.T. (2025)
Food insecurity remains a major challenge in Africa, disproportionately affecting women and children. Despite their favorable nutrient profiles for underutilized legumes especially Bambara groundnut (Vigna subterranea), African yam bean (Sphenostylis stenocarpa), and lima bean (Phaseolus lunatus) are rarely consumed in Nigerian diets. This study assessed socio-economic determinants, awareness, perceived benefits, and consumption patterns of these legumes among women in Niger State. A cross-sectional survey of 420 rural and 420 urban women were conducted using stratified random sampling, interviewer-administered questionnaires divided into socio-demographics, legume awareness, consumption behaviors, and perceived drivers section. Data were analyzed in R Studio using descriptive statistics, Spearman correlation, and path coefficient analyses. Awareness was highest for Bambara groundnut, moderate for lima bean, and lowest for African yam bean. Educated women had greater nutrition knowledge than those with less schooling. Bambara groundnut was consumed two to four times weekly by 68% of rural women but 15% of urban women; African yam bean and lima bean consumption were mostly seasonal. Among rural women, religion strongly influenced Bambara groundnut consumption, while occupation and religion were correlated of lima bean intake. In contract, among urban women, none of the demographic factors was statistically significant predictors of African Yam Bean and Bambara Groundnut but Lima Bean consumption was influenced by Education and Religion. The Key barriers included cooking difficulty, antinutritional factors, and limited perceived benefits in both rural and urban areas. Targeted nutrition education is needed to raise awareness, and increase consumption of underutilized legumes among women in Niger State, Nigeria.